2007
DOI: 10.1021/jm070876h
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyano- and Amidino-Substituted Derivatives of Styryl-2-Benzimidazoles and Benzimidazo[1,2-a]quinolines. Synthesis, Photochemical Synthesis, DNA Binding, and Antitumor Evaluation, Part 3

Abstract: Synthesis of novel cyano- and amidino-substituted styryl-2-benzimidazoles and benzimidazo[1,2-a]quinolines by condensation reactions and photochemical dehydrocyclization and dehydrohalogenation cyclization is described. Thermal denaturation experiments reveal that cyclic derivatives considerably stabilize DNA double helix, while the effect of their acyclic analogues is negligible. According to the spectroscopic study of the interaction of cyclic derivative 19, we propose intercalation of benzimidazo[1,2-a]quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 243 publications
(131 citation statements)
references
References 43 publications
5
121
0
4
Order By: Relevance
“…Novel amidino-substituted derivative of benzimidazo [1,2-a]quinoline was synthesized in the group of Professor Grace Karminski-Zamola (Department of Organic Chemistry, Faculty of Chemical Engineering and Technology in Zagreb) as described previously (1).…”
Section: Test Compoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel amidino-substituted derivative of benzimidazo [1,2-a]quinoline was synthesized in the group of Professor Grace Karminski-Zamola (Department of Organic Chemistry, Faculty of Chemical Engineering and Technology in Zagreb) as described previously (1).…”
Section: Test Compoundmentioning
confidence: 99%
“…Results were expressed as IC 50 (the concentration that causes 50% growth inhibition) calculated from the dose-response curves using linear regression analysis (1).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 As a part of our continuing search for potential anticancer agents related to benzimidazole derivatives, we have recently reported on the synthesis, cytostatic evaluation, DNA/RNA interaction study and proteomic profiling of a series of amidino-substituted heterocyclic benzimidazoles and benzimidazo [1,2-a]quinolines. 15,16 Biological study confirmed the anticancer potential of this class of compounds, especially that of positively charged analogues of benzimidazo [1,2-a]quinolines which intercalate into ds DNA or RNA.…”
Section: Introductionmentioning
confidence: 77%
“…The growth inhibition activity was assessed as described previously [ 7,8,15,16,20 ]. The panel cell lines were inoculated onto a series of standard 96-well microtiter plates on day 0, at 1×10 4 to 3×10 4 cells/mL, depending on the doubling times of a specific cell line.…”
Section: Antitumor Evaluation Assaymentioning
confidence: 99%